HRM in foreign affiliates: A multiple case study among Estonian affiliates of Finnish companies - Ervasti Mia; Vesa Suutari (Journal for East European Management Studies, 2004)
The key question concerning the HRM in MNCs is the extent of global standardization versus localization of HRM-practices. The present study analyses whether the Finnish companies operating in Estonia apply a clear strategical approach to their IHRM and if so, what kind of approach (standardization versus localization) they have adopted across key HRMfunctions. The study followed a qualitative multiple case study approach. The results of the study showed that case companies did not have one clear approach to HRM in foreign affiliates in Estonia, i.e. those had not systematically standardized or localized all the HRM-functions. – – Ein wichtiges Kriterium im Personalmanagement in multinationalen Unternehmen ist die Gegenüberstellung des Ausmasses der globalen Standardisierung im Vergleich zur Lokalisierung von HRM-Praktiken. Die vorliegende Studie analysiert, ob die finnischen Unternehmen in Estland eine klare Strategie im Hinblick auf ihr HRM verfolgen und falls ja, welche Art von Ansatz (Standardisierung oder Anpassung an örtliche Begebenheiten) sie für Schlüsselfunktionen im HRM genutzt haben. Die Studie basiert auf mehreren Fallstudien. Die Ergebnisse zeigen auf, dass die untersuchten Firmen keinen klaren Ansatz für das HRM in ausländischen Tochterfirmen in Estland haben, d.h. sie haben ihre HRM-Funktionen weder systematisch standardisiert noch lokalisiert.
Keywords: 650; HRM; MNC; Finland; Estonia; standardization; localization